PERBAIKAN PADI (Oryza sativa L.) VARIETAS CIHERANG UNTUK SIFAT UMUR GENJAH DAN PRODUKSI TINGGI MENGGUNAKAN MARKA MOLEKULER - Prasetiyono, Joko; Tasliah, Tasliah; Dadang, Ahmad; Fatimah, Fatimah (Research Center for Biology-Indonesian Institute of Sciences, 2013)
The improvement of rice (Oryza sativa L.) Ciherang variety for early maturity and high production traits was carried out by Marker Assisted Backcrossing (MAB) method using Nipponbare as donor parent. The foreground selection of Hd2 gene was laid on flanking markers of RM1362 and RM7601 in QTL region. The selection process of F1 to BC2F2 plants were based on molecular markers and agronomic characters. The BC2F3 plants were challenged to bacterial leaf blight to know their resistance in this hybridization. The results indicated that the foreground and background selection were not sufficient as selection tools therefore they would be more accurate if assosiated with agronomic characters. Four selected lines derived from Ciherang x Nipponbare crossed (BC2F3 plant # 283, 307, 373, and 462) could be promising lines with early maturity and high productioncompared to Ciherang. Selected BC2F3 lines flowered earlier than original Ciherang up to 7-10 days, while the yield increasing was 3.55 to 9.2% higher based on weight of filled grains/plant, and from 3.58 to 19.39% higher based on the number of filled grain/plant. However, all of BC2F3 lines were not resistant to bacterial leaf blight attack.